Characterization of the respiration‐induced yeast mitochondrial permeability transition pore. Issue 12 (22nd November 2013) - Bradshaw, Patrick C.; Pfeiffer, Douglas R.
Abstract When isolated mitochondria from the yeast Saccharomyces cerevisiae oxidize respiratory substrates in the absence of phosphate and ADP, the yeast mitochondrial unselective channel, also called the yeast permeability transition pore (yPTP), opens in the inner membrane, dissipating the electrochemical gradient. ATP also induces yPTP opening. yPTP opening allows mannitol transport into isolated mitochondria of laboratory yeast strains, but mannitol is not readily permeable through the yPTP in an industrial yeast strain, Yeast Foam. The presence of oligomycin, an inhibitor of ATP synthase, allowed for respiration‐induced mannitol permeability in mitochondria from this strain. Potassium (K+) had varied effects on the respiration‐induced yPTP, depending on the concentration of the respiratory substrate added. At low respiratory substrate concentrations K+ inhibited respiration‐induced yPTP opening, while at high substrate concentrations this effect diminished. However, at the high respiratory substrate concentrations, the presence of K+ partially prevented phosphate inhibition of yPTP opening. Phosphate was found to inhibit respiration‐induced yPTP opening by binding a site on the matrix space side of the inner membrane in addition to its known inhibitory effect of donating protons to the matrix space to prevent the pH change necessary for yPTP opening. The respiration‐induced yPTP was also inhibited by NAD, Mg2+, NH4+ or the oxyanion vanadate polymerized to decavanadate. The results demonstrate similar effectors of the respiration‐induced yPTP as those previously described for the ATP‐induced yPTP and reconcile previous strain‐dependent differences in yPTP solute selectivity. Copyright © 2013 John Wiley & Sons, Ltd.